Evaluation of single‐use tangential flow filtration technology for purification of activated polysaccharides used in conjugate vaccine manufacturing. (21st September 2021) - Motevalian, Seyed Pouria; Steen, Jonathan; De Leon, Janine; Sriskanda, Verl; Carino, Ivette; Prashad, Amar S.; Carrillo Conde, Brenda; Arve, Bo
Abstract: Over the past decade, single‐use tangential flow filtration (TFF) technologies have emerged to reduce system preparation time, promote fast and flexible product change over, and ultimately shorten process development and manufacturing time/cost. In this study, the performance of a recently developed Pellicon® single‐use TFF capsule was compared against traditional Pellicon® cassettes by assessing TFF process performance (such as flux, residuals clearance, and yield) and post‐purification product attributes (such as concentration and mass‐weighted average molecular weight). Good scaling was shown by comparing process performance and product attributes across different scales and formats. Additionally, similar TFF process performance and post‐purification product attributes were observed for the single‐use capsule compared to the reusable TFF cassettes. The capsule requires a smaller flush than the cassette, and it is easier to use since it does not require a compression holder or pre‐sanitization. The results provide insight into the application of the single‐use TFF capsule and scalability of TFF processes for the purification of conjugate vaccines.